Sensitive determination of lead, cadmium and nickel in soil, water, vegetable and fruit samples using STAT-FAAS after preconcentration with activated carbon - Keskin, Gulbahar; Bakirdere, Sezgin; Yaman, Mehmet (Sage Publications Inc, 2015)
In this study, lead (Pb), cadmium (Cd) and nickel (Ni) were determined in soil, water, vegetable and fruit samples taken from around oil refinery region in Batman, Turkey. Digestion procedures for samples were optimized and all optimum parameters were used both in digestion and in determination steps. In order to determine Pb and Cd, slotted tube atom trap (STAT) was used to increase the sensitivity in atomic absorption spectrophotometry. Preconcentration procedure under the optimum conditions was applied to water, vegetable and fruit samples to determine Pb, Cd and Ni in trace levels. In soil samples, concentrations of analytes were found in the range of 4.0 +/- 0.2-12,000 +/- 60 mg/kg for Pb, 0.15 +/- 0.01-3.0 +/- 0.1 mg/kg for Cd and 21 +/- 1-65 +/- 3.4 mg/kg for Ni. In all water samples, concentration of Ni was expressed as nanogram per milliliter (ng/mL) and found to be higher than Pb and Cd levels. It was observed that Pb, Cd and Ni concentrations varied from both plant to plant and in same plants at different experimental sites. Pb concentrations in vegetable and fruit samples interested varied between 20 +/- 2 and 160 +/- 12 ng/g, and the highest level of Pb was found to be in green pepper taken from 1000 m away from refinery.
Keywords: Lead; cadmium; nickel; soil; vegetable